2021
DOI: 10.1038/s41391-021-00391-8
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic power of 18F-FDG PET/CT extends to estimating systemic treatment response duration in metastatic castration-resistant prostate cancer (mCRPC) patients

Abstract: Background We aimed to test whether the prognostic value of 18 F‐Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (FDG-PET/CT) in metastatic castration-resistant prostate cancer (mCRPC) extends to the estimation of systemic treatment response duration. Methods mCRPC patients submitted to FDG-PET/CT in four Italian centers from 2005 to 2020 were retrospectively enrolled. Clinical and biochemical data at the time of imaging were collected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…On the other hand, many studies already showed the prognostic value of circulating PSA and ALP at baseline, as biochemical indicators of the tumor extent [28,[31][32][33][34][35][36][37][38]. This is coherent with the unfavorable prognosis observed in patients with massive bone metastases (> 20) at the bone scan or high tumor burden assessed with more sophisticated quantification approaches [32,[39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, many studies already showed the prognostic value of circulating PSA and ALP at baseline, as biochemical indicators of the tumor extent [28,[31][32][33][34][35][36][37][38]. This is coherent with the unfavorable prognosis observed in patients with massive bone metastases (> 20) at the bone scan or high tumor burden assessed with more sophisticated quantification approaches [32,[39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 83%
“…Standardised uptake value (SUV) max of identified tumours is a prognostic imaging biomarker ( 108 ), and when measured from [ 18 F]-fluorodeoxyglucose (FDG) PET-avid lesions has been shown to correlate with patient survival ( 109 ). Total lesion glycolysis (TLG) or total SUV (SUV total ), measured as the sum of individual SUVs in each voxel for each individual lesion, is another prognostic imaging biomarker that has been shown to correlate with overall survival in metastatic castration-resistant prostate cancer (mCRPC) patients ( 110 ). Radiomics possesses great potential because rather than attempting to replace these biomarkers, clinicopathologic risk factors and patient characteristics can be incorporated into the modelling process and leveraged to make better model predictions.…”
Section: Conventional Mpca Biomarkers and Risk Factors – A Brief Overviewmentioning
confidence: 99%
“…However, in addition to the specificity of these tracers for the prostatic tissues, PSMA molecules can be concentrated even by a wide range of solid and haematologic malignancies due to its expression by the cancer neovascularization, in the absence of a specific receptor-mediated mechanism [7][8][9]. Conversely, in contrast with the advanced metastatic hormone-refractory stage [10][11][12], the low 18F-FDG-avidity of well-differentiated, low-grade, naïve prostate cancer makes this tool not routinely recommended in this clinical setting [13]. The divergent uptake pattern of the two radiotracers thus raised the suspicion of the coexistence of two different tumour entities, which were subsequently pathologically confirmed.…”
Section: Discussionmentioning
confidence: 99%